2022
DOI: 10.1186/s43162-022-00099-8
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic gap and the outcome of diabetic patients presenting with acute coronary syndrome

Abstract: Background Acute hyperglycemia is a common finding in both diabetic and non-diabetic patients with acute coronary syndrome (ACS) who present to the emergency department (ED). The prognostic role of hyperglycemia in diabetic patients with ACS remains controversial at least on the short-term basis. The aim of the present study was to find the relation between the glycemic gap and clinical outcome in diabetic patients with ACS. Methods The study inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…On the contrary, spontaneous hypoglycemia is also happened to be a risk factor for mortality following MI [ 20 ]. While some studies also reported short and long-term outcomes of AMI by using glycemic gap [ 21 , 22 ]. There is also uncertainty over diagnosing incident diabetes during acute myocardial event among previously undiagnosed cases [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, spontaneous hypoglycemia is also happened to be a risk factor for mortality following MI [ 20 ]. While some studies also reported short and long-term outcomes of AMI by using glycemic gap [ 21 , 22 ]. There is also uncertainty over diagnosing incident diabetes during acute myocardial event among previously undiagnosed cases [ 23 ].…”
Section: Discussionmentioning
confidence: 99%